Cytomorphological spectrum of head and neck lesions by fine needle aspiration cytology in a tertiary care center - Amandeep Kaur; Sonali Poonia; Karandeep Singh; Dalbir Kaur; Mohit Madhukar; Ravish Godara (Wolters Kluwer Medknow Publications, 2023)
Introduction: Fine needle aspiration cytology (FNAC) is considered the first line investigation of choice for evaluating head and neck swellings as it is a quick, safe, and rapid diagnostic procedure. Material and Methods: This is a retrospective study that included 242 cases of head and neck lesions in the Department of Pathology, Maharaja Agrasen Medical College, Agroha. FNAC was performed by aspiration and non aspiration techniques, and cytological diagnosis was given and correlated with clinical findings and investigations. Results: The most common age group affected was 21-30 years. Male to female ratio was 1:1.49. Out of 242 cases, maximum lesions were found in lymph nodes (128 cases), followed by thyroid gland in 81 cases, salivary gland in 23 cases, and miscellaneous group in 10 cases. Maximum number of cases reported were inflammatory (55.37%), followed by benign (29.33%) and malignant (11.15%) cases. Most swellings occurring in the head and neck region are inflammatory in nature. Conclusion: Our study concluded that FNAC is a simple, safe, and minimal invasive technique that differentiates between neoplastic and non neoplastic lesions and avoids unnecessary surgeries.